DESAIN BUCK-BOOST CHOPPER SEBAGAI MPPT BERBASIS MIKROKONTROLER - Slamet, Riyadi; Fl. Budi, Seiawan (Seri Kajian Ilmiah, 2013)
This paper describes a buck-boost chopper that can be implemented as maximum power point tracker (MPPT). This can be connected to the load which are greater or less than MPP resistance. The control of this device is based on microcontroller so it is very simple and cheap. Analysis is done to give basic theory and finally simulation and laboratory experiment are done to verify. Based on the results, the chopper is able to give gain less or greater than unity.